US regulatory compliance for medical combination products: an overview - Singh, Manav V.; Apshingekar, Prafulla; Gandhi, Sanyam; Singh, Om V. (Frontiers in medical technology, 2024)
This article provides a high-level overview of US regulatory review and approval processes for the growing field of medical combination products (CPs; those merging drugs with devices and/or biological products). US law defines drugs, medical devices, and CPs in specific ways, and the components of a CP are still subject to their respective regulations while combined. The Food and Drug Administration's Office of Combination Products (OCP) oversees the review and classification of CPs, which is based on their primary mode of action. When a manufacturer submits a Request for Designation for a new CP, the OCP conducts a technical and clinical evaluation to identify risks and verify modes of action and therapeutic benefits. Evaluating the safety and efficacy of CPs and their constituent parts can be challenging due to the many potential interactions. However, as innovation continues in the health care landscape and the variety of CPs on the market increases, manufacturers must stay proactive in complying with regulatory standards and keeping their products safe.